Risk and protective factors associated with intentional self‐harm among older community‐residing home care clients in Ontario, Canada. (6th February 2015) - Neufeld, Eva; Hirdes, John P.; Perlman, Christopher M.; Rabinowitz, Terry
<x xml:space="preserve">Abstract</x> Objective We aim to concurrently examine risk and protective factors associated with intentional self‐harm among community‐residing older adults receiving home care services in Ontario, Canada. Methods Administrative health data from the home care sector were linked to hospital administrative data to carry out the analyses. Home care data are collected in Ontario using the Resident Assessment Instrument—Home Care (RAI‐HC), an assessment tool that identifies strengths, preferences and needs of long‐stay home care clients. The sample included Ontario home care clients aged 60 years or older assessed with the RAI‐HC between 2007 and 2010 (N = 222, 149). Multivariable analyses were performed using SAS. Results Hospital records of intentional self‐harm (ISH) were present in 9.3 cases per 1000 home care clients. Risks of ISH included younger age (60–74 years; OR = 3.14, CI: 2.75–3.59), psychiatric diagnosis (OR = 2.29, CI: 2.06–2.54), alcohol use and dependence (OR = 1.69, CI: 1.34–2.14), psychotropic medication (OR = 1.94, CI: 1.75–2.15) and depressive symptoms (OR = 1.58, CI: 1.40–1.78). Protective effects were found for marital status and positive social relationships, yet these effects were more pronounced for men. Cognitive performance measures showed the odds of ISH 1.86 times higher for older adults with moderate to severe cognitive impairment. Conclusions This study based on provincial data points to tangible areas for preventative assessment by frontline home care professionals. Of interest were the risk and protective factors that differed by sex. As demand for home care in Canada is expected to increase, these findings may inform home care professionals' appraisal and approach to suicide prevention among community‐residing older adults. Copyright © 2015 John Wiley & Sons, Ltd.